Natural Dye Production from Beetroot Using Vinegar and Non-Solvent : pH and Colorfastness Testing on White Fabric - Rabiah Afifah Daulay; Sophia Gloria Bakara; Nailatul Fauzah Ritonga; Siti Khailafizah; Sofia Ramadhani; Suci Trianata Situmorang; Moondra Zubir; Abd Hakim S (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Natural dyes derived from plants are increasingly attractive due to their safety and environmental friendliness. This study aimed to investigate the effect of vinegar as a natural solvent on the colorfastness of beetroot (Beta vulgaris L.) dye applied to white fabric. The research involved extracting pigments from beetroot, applying them to fabric, and testing the solution’s pH, drying time, and wash fastness. The results showed that pure beetroot extract had a pH of 5.2, while the addition of vinegar reduced the pH to 2.5–3.1. Fabric dyed with beetroot + vinegar exhibited higher initial color intensity (score 11) compared to pure beetroot (score 9), but its colorfastness dropped sharply after washing (score 4 vs. 7). Vinegar addition also prolonged fabric drying time from 12 minutes (without vinegar) to 17.5 minutes (with 20 mL vinegar). These findings indicate that vinegar enhances initial dye brightness but reduces colorfastness after washing. Nevertheless, beetroot dye remains a safer and eco-friendly alternative to synthetic dyes, although further optimization is required to improve its durability.